A national cohort study evaluating infant and fetal mortality caused by birth defects in Korea. Issue 11 (15th November 2017) - Ko, Hyun Sun; Kim, Dong Joo; Chung, Yoohyun; Wie, Jeong Ha; Choi, Sae Kyung; Park, In Yarg; Park, Yong Gyu; Shin, Jong Chul
Abstract : Objective: To analyse the prevalence of fetal and infant deaths due to birth defects in Korea and those trends according to maternal age. Design: Retrospective national cohort study Setting: Korean Vital Statistics database of the Korean Statistical Information Service, between 2009 and 2015. Participants: 2176 infant deaths and 4343 fetal deaths caused by birth defects, among 3 181 145 total live births and 43 385 fetal deaths during the study periods. Methods: Infant and fetal mortality rates (IMRs and FMRs) by birth defects, from deaths caused by birth defects, were analysed. They were compared, according to maternal age groups: (I) '10–19 years'; (II) '20–29 years'; (III) '30–34 years'; (IV) '35–39 years'; and (V) '40–55 years'. Main outcome measures: IMRs and FMRs by birth defects and comparison according to maternal age group. Results: IMRs and FMRs by birth defects were 6.84 per 10 000 live births and 13.47 per 10 000 total births. The most common causes of infant deaths and fetal deaths by birth defect were anomaly of the circulatory system (51.1%, IMR 3.5) and chromosomal abnormality (33.1%, FMR 4.46), respectively. Among groups by maternal age, FMRs by birth defects were significantly higher in groups I and V compared with group III (OR 6.59, 95% CI 3.49 to 12.43; and OR 3.46, 95% CI 1.77 to 6.78, respectively). IMR and FMR by nervous system anomaly were significantly higher in group I at 3.63 (OR 2.0, 95% CI 1.97 to 2.03) and 29.84 (OR 15.04, 95% CI 3.59 to 62.96) compared with 0.32 and 1.97 in group III. Conclusion: FMRs by birth defects were the highest in the extreme maternal age groups. Severe anomalies, except for chromosomal abnormality, were most prevalent in teenage pregnancies.